“LISTENING IS EVERYTHING”: connected listening paths in the articulations between playlists, pre-saves and musical recommendations on Spotify - Pires, Victor de Almeida Nobre (2022)
This work proposes a reflection on the negotiations between productive practices in the music universe, online platforms, algorithms and recommendation systems based on the articulation between pre-save and playlists. It is interesting to think how the centrality of playlists in contemporary listening paths impacts on the strategies of musical production and dissemination. Thus, this article pays attention to new relationships between datification of music consumption and recommendations practices of online platforms.